After the Charities' Act: Governance and Decision-making in Britain Yearly Meeting of the Religious Society of Friends (Quakers). Issue 2 (December 2019) - Cummins, Penelope
Abstract : Conforming to the Charity Commission's governance requirements in terms of the Charity Acts of 1993 and 2006, the Religious Society of Friends in Britain (Quakers) introduced a small trustee body to take strategic responsibility for the management of its national activities. This article traces some of the decisions made by trustees and finds that the centralisation of decision-making has substantially changed the role and authority of the wider membership. It is suggested that this is a manifestation of secularisation through conformity to external, state requirements as described by Bryan Wilson and Steve Bruce.